Characterization of a thermally stable red-light-emitting phosphor: synthesis, photoluminescence, and thermoluminescence studies of CsCaF3 compound doped with Eu3+ for solid-state lighting applications - N. Hema; B. Chandrasekaran; R. Kameshwaran; M. Ammal Dhanalakshmi; V. Rathina Mala; G. Annadurai; K. Ganesh Kumar; M. Vimalan; Mohammed F. Albeshr (Journal of Information Display)
In this investigation, we focused on the synthesis and characterization of CsCaF3 compound doped with europium (Eu3+) ions using a solid-state route. To analyze the crystal structure of the synthesized phosphors, X-ray diffraction analysis was employed. Additionally, the doped sample underwent examination of surface morphology and elemental composition through Field Emission Scanning Electron Microscopy and EDAX mapping. The color of the pure and doped CsCaF3 sample was quantified and fitted using Color coordinate graph by the Commission Internationale de l'Eclairage (CIE). The red emission on the doped CsCaF3 compound was detected at 465 nm, which is the transition from 5D0 to 7Fj (j = 0, 1, 2, and 3). The 0.5 mol. % Eu3+ doped CsCaF3 sample was found to have a color purity of 81% and an associated color temperature of 1660 K, indicating its suitability for aesthetic lighting applications. Furthermore, thermoluminescence study, electron paramagnetic resonance (EPR), and effective atomic number (Zeff) calculations were conducted to provide valuable information for potential radiation dosimetry applications.